In Silico Screening, Synthesis and In Vitro Evaluation of Some Quinazolinone and Pyridine Derivatives as Dihydrofolate Reductase Inhibitors for Anticancer Activity - A. G. Nerkar; A. K. Saxena; S. A. Ghone; A. K. Thaker (E-Journal of Chemistry)
Dihydrofolate reductase (DHFR) is the important target for anticancer drugs belonging to the class of antimetabolites as the enzyme plays important role in the de novo purine synthesis. We here report the in silico screening to obtain best fit molecules as DHFR inhibitors, synthesis of some ʻbest fitʼ quinazolinone from 2-phenyl-3-(substituted-benzilidine-amino) quinazolinones (Quinazolinone Shiff's bases) QSB1-5 and pyridine-4-carbohydrazide Shiff's bases (ISB1-5) derivatives and their in vitro anticancer assay. Synthesis of the molecules was performed using microwave assisted synthesis. The structures of these molecules were elucidated by IR and 1H-NMR. These compounds were then subjected for in vitro anticancer evaluation against five human cancer cell-lines for anticancer cyto-toxicity assay. Methotrexate (MTX) was used as standard for this evaluation to give a comparable inhibition of the cell proliferation by DHFR inhibition. Placlitaxel, adriamycin and 5-fluoro-uracil were also used as standard to give a comparable activity of these compounds with other mechanism of anticancer activity. ISB3 (4-(N, N-dimethyl-amino)-phenyl) Schiff''s base derivative of pyridine carbohydrazide showed equipotent activity with the standards used in in vitro anticancer assay as per the NCI (National Cancer Institute) guidelines.